Penyuluhan Dan Konseling Dalam Meningkatkan Kepedulian Sosial Lansia Di Kelurahan Meruya Selatan Jakarta - Monica Dwi Hartanti; Sisca; Wita Anggraini; Dyani Pitra Velyani; Joey Joshua Vidova Tjahyadi (AMMA : Jurnal Pengabdian Masyarakat, 2024)
The increase in the elderly population in Meruya Selatan Subdistrict, Jakarta, demands efforts to increase their social awareness and welfare. This research aims to evaluate the effectiveness of outreach and counseling in improving the social care of the elderly in the area. The methods used include data collection on the elderly, conducting workshops, individual and group counseling sessions, as well as developing social and recreational activities.The results showed an increase in the social participation of elderly people, a decrease in loneliness levels, and an increase in psychological well-being. Seniors who take part in the program demonstrate active involvement in community activities and have a better understanding of the importance of physical and mental health. Challenges faced include limited resources and difficulty mobilizing participants. This program has succeeded in improving the quality of life of the elderly through a comprehensive and collaborative approach. Recommendations for further development include increasing the capacity of the extension team and counselors, utilizing digital technology, and developing infrastructure that is elderly friendly. This research underscores the importance of ongoing and collaborative social support for the well-being of older adults.